The relationship between nutritional status, serum folic acid and homocyteine levels in hemodialysis and peritoneal dialysis patients: Nutritional status, serum folic acid and homocyteine levels - Akalin, Handan; Rakicioğlu, Neslişah (Progress in Nutrition, 2020)
Background. Nutritional deficiencies and imbalances may be encountered in hemodialysis (HD) and peritoneal dialysis (PD) patients. The aim of this study is to investigate the relationship between nutritional status, and serum folic acid and homocysteine levels in hemodialysis and peritoneal dialysis patients. Methods. Information about demographics and eating habits were recorded using a questionnaire in 30 hemodialysis and 30 peritoneal dialysis patients. The subjective global assessment was used to assess the nutritional status of the patients. Individual food consumption records were taken in three consecutive days. Some routine blood parameters were recorded from the patient files. Folic acid, vitamin B12 and homocysteine analysis were also performed from the serum samples from the remaining blood. Results. All of the dialysis patients were found malnourished. Body weight, body mass index, waist and hip circumferences values was lower HD patients than PD patients (p<0.05). Serum homocysteine levels of PD patients were higher than HD patients (p<0.05). A positive correlation was identified between serum homocysteine and BUN levels, whereas there was an inverse relationship between homocysteine and vitamin B12 level, total protein, albumin level and malnutrition score (p<0.05). In general, no significant difference was found between the nutrients intake of HD and PD patients. Conclusion. Nutritional status of patients of HD was found better than PD patients. Assessment of nutritional status periodically is important for the prevention of malnutrition and early intervention in dialysis patients. Dietary folic acid, vitamin B12, vitamin B6 and protein intake may be improved by foods or supplementation for prevention of hyperhomocysteinemia in dialysis patients.